Repeated dose toxicity study to assess the safety and reproductive/developmental safety of 7-methyl-2H-1, 5-Benzodioxepin-3(4H)-One (Calone®) and the read across approach to its biodegradation metabolite 7-methyl-2H-1, 5-benzodioxepin-3-ol (Calol). (October 2022) - Liu, Hanghui; Ida, Lily; Birkbeck, Anthony A.; Lantto, Tiina A.; Etter, Sylvain; Delaney, Bryan
Abstract: 7-Methyl-2H-1, 5-benzodioxepin-3(4H)-one (Calone®) is used in fragrances to impart a marine note. It is produced industrially at volumes requiring repeated dose and developmental/reproductive toxicology data (OECD TG 422) under European chemicals legislation (i.e., REACH). Additionally, Japanese chemicals legislation requires evaluation of Calone® biodegradability and identification of metabolites in an environmental biodegradation test. 7-Methyl-2H-1, 5-benzodioxepin-3-ol (Calol) was the sole metabolite identified following biodegradation and a 28-day repeated dose toxicity study (OECD TG 407) would normally be required to support registration in Japan. The current paper presents results showing no adverse effects in the parental, reproductive, or developmental phases of an OECD TG 422 study following dietary administration of Calone® to rats at targeted doses of up to 1000 mg/kg/day. The No Observed Adverse Effect Level (NOAEL) was the highest administered dose of 791 and 922 mg/kg/day for males and females, respectively. An i n vitro metabolism study conducted with rat and human liver microsomes demonstrated that greater than 90% of Calone® was metabolically reduced into Calol, the same metabolite observed in the environmental biodegradation test. Accordingly, the results from the OECD TG 422 study with Calone® are directly applicable to Calol and it would be expected to have the same NOAEL.